Financial Performance Trends Comparison: Mining Versus Property Sector During Global Recession (International Forum of Researchers and Lecturers, 2024)
The purpose of this study is to determine the effect of ROA, ROE, NPM, GPM, cash ratio, quick ratio, current ratio, TDTA, and DER ratios on the financial performance of property versus mining companies in the event of a global recession. The dependent variable studied is financial performance, while the independent variables are ROA, ROE, NPM, GPM, cash ratio, quick ratio, current ratio, TDTA, and DER. The theories used are agency theory, legitimacy theory, and stakeholder theory. We conducted quantitative comparative research. This study uses a sample of 34 property companies and 37 mining companies from 2018 to 2023. The data analysis of this study employs the EViews program for statistical calculations. The results of the study indicate that ROA, ROE, NPM, cash ratio, and quick ratio in the mining sector are better than in the property sector. Meanwhile, the GPM, current ratio, TDTA, and DER ratios in the property sector show better values compared to the mining sector. The Mann-Whitney Test results indicate that ROA, ROE, NPM, GPM, cash ratio, quick ratio, current ratio, TDTA, and DER significantly affect financial performance in facing global crises.